2005
DOI: 10.1007/s00125-005-1917-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of a polymorphism in the gene encoding phosphoenolpyruvate carboxykinase 1 with high-density lipoprotein and triglyceride levels

Abstract: Aims/hypothesis: Phosphoenolpyruvate carboxykinase (PCK) is the key enzyme involved in the regulation of gluconeogenesis. The aim of this study was to identify genetic polymorphisms in potential candidate genes for type 2 diabetes by sequencing all exons in the PCK genes (PCK1 and PCK2), and examining the association with type 2 diabetes and diabetic phenotypes in a Korean population (775 type 2 diabetic patients and 316 normal control subjects). Materials and methods: Twenty-two polymorphisms in PCK1 and PCK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Despite strong evidence from animal studies (11,12,13), we could not find any evidence for the association of PCK1 variants with obesity‐related phenotypes in children and adolescents. Previous studies have shown association between genetic variation in PCK1 and the risk of type 2 diabetes and related traits (4,17,18,19,20), of which we genotyped four (rs6070157, rs2179706, rs1042531, and rs707555) but found no evidence for association in the EYHS. As this is the first study examining the association of genetic variants in PCK1 gene with obesity in young individuals, more studies are needed to explore the association of PCK1 gene variants with obesity‐related phenotypes in other populations.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Despite strong evidence from animal studies (11,12,13), we could not find any evidence for the association of PCK1 variants with obesity‐related phenotypes in children and adolescents. Previous studies have shown association between genetic variation in PCK1 and the risk of type 2 diabetes and related traits (4,17,18,19,20), of which we genotyped four (rs6070157, rs2179706, rs1042531, and rs707555) but found no evidence for association in the EYHS. As this is the first study examining the association of genetic variants in PCK1 gene with obesity in young individuals, more studies are needed to explore the association of PCK1 gene variants with obesity‐related phenotypes in other populations.…”
Section: Discussionmentioning
confidence: 63%
“…Regions near the PCK1 locus on human chromosome 20 have been implicated in obesity (16). In addition, several studies in humans have shown associations of specific polymorphsims in the PCK1 gene with type 2 diabetes and related metabolic traits (4,17,18,19,20). However, the present study investigates the association of single‐nucleotide polymorphisms (SNPs) in the PCK1 gene with obesity, PA, and fitness and examines the interaction between the PCK1 SNPs, and PA and fitness on obesity risk in the European Youth Heart Study (EYHS), a large population‐based study of children and adolescents from Denmark and Estonia.…”
Section: Introductionmentioning
confidence: 99%
“…As with many genetic association studies investigating polygenic diseases, attempts to replicate the association between PCK1 and T2D have produced mixed results. A haplotype of PCK1 variants was shown to confer risk of developing the disease in a Korean population (OR not given, p = 6 × 10 -3 ) [ 5 ], and a screen of 134 candidate susceptibility SNPs showed that the -232C/G SNP was a risk factor for T2D in a Finnish cohort (OR = 1.27, 95% CI 1.02 - 1.57, p = 0.031) [ 6 ]. A recent study reported that multiple PCK1 variants are associated with T2D in a Chinese population [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for a promoter polymorphism, −232C > G, the minor G allele was reported to associate with Type 2 diabetes in 375 Canadian Caucasians as well as in 562 subjects in the Canadian Oji‐Cree population, and the polymorphism was shown to be functional in studies of mouse preadipocytes [9]. No association between Type 2 diabetes and the −232C > G polymorphism was observed in Japanese or Korean study populations [10,11]; however, in the Japanese cohort, age of clinical onset of Type 2 diabetes was significantly lower among carriers of the G allele [10].…”
Section: Introductionmentioning
confidence: 99%